2020
DOI: 10.1063/5.0010254
|View full text |Cite
|
Sign up to set email alerts
|

Peak thermoelectric power factor of holey silicon films

Abstract: The thermoelectric properties of nanostructured silicon are not fully understood despite their initial promise. While the anomalously low thermal conductivity has attracted much work, the impact of nanostructuring on the power factor has mostly escaped attention. While initial reports did not find any significant changes to the power factor compared to the bulk, subsequent detailed measurements on p-type silicon nanowires showed a stark reduction in the Seebeck coefficient when compared to similarly doped bulk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…According to spectral scaling model [18], [34], a 20 nm neck size, 30 µm thickness, and 30% porosity of holey silicon result in an in-plane thermal conductivity of 1 W/mK and a cross-plane thermal conductivity of 13 W/mK. Previous thermal conductivity measurement of holey silicon also supports these values [24], [27]. P-type single-crystal silicon with a doping concentration of 2.5 × 10 19 cm −3 is assumed in this model, providing an electrical conductivity of 2.52 × 10 4 S/m and a Seebeck coefficient of 440 µV/K in bulk silicon, as is experimentally reported in literature [35], [36], [37].…”
Section: A Soi Transistor-tec Devicementioning
confidence: 79%
See 1 more Smart Citation
“…According to spectral scaling model [18], [34], a 20 nm neck size, 30 µm thickness, and 30% porosity of holey silicon result in an in-plane thermal conductivity of 1 W/mK and a cross-plane thermal conductivity of 13 W/mK. Previous thermal conductivity measurement of holey silicon also supports these values [24], [27]. P-type single-crystal silicon with a doping concentration of 2.5 × 10 19 cm −3 is assumed in this model, providing an electrical conductivity of 2.52 × 10 4 S/m and a Seebeck coefficient of 440 µV/K in bulk silicon, as is experimentally reported in literature [35], [36], [37].…”
Section: A Soi Transistor-tec Devicementioning
confidence: 79%
“…While significant advancements have been made in enhancing the ZT value through nanostructuring [21] and controlled doping [22], most conventional thermoelectric materials are not compatible with microelectronic manufacturing processes. However, holey silicon stands out as one of the few candidates that offers a unique combination of high thermoelectric performance (theoretical ZT ∼ 0.47 at 300 K) [23], [24], [25] and excellent compatibility with the bipolar-CMOS-DMOS (BCD) technology. Experimental results and analytical models have demonstrated that the holey silicon thin film, possessing optimal neck size, and porosity, exhibits not only low in-plane thermal conductivity (1-10 W/mK at 300 K) but also high electrical conductivity and Seebeck coefficient inherited from bulk silicon [18], [23], [24], [25], [26], [27].…”
mentioning
confidence: 99%
“…In addition to our data, the graph also displays information on p-type nanostructured silicon. Specifically, it includes results from studies involving nanowires, 26,52 holey silicon, 32,[53][54][55] and ultrathin solid films. The presence of phonon drags near room temperature in membranes has provided an opportunity to Fig.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Since, in silicon, thermal conductivity is largely due to heat transported by long MFP phonons, this leads to a major κ reduction. An alternative strategy involves top-down control to generate nanopores in 'holey' silicon, reducing κ without adversely affecting the power factor [8,9].…”
Section: Introductionmentioning
confidence: 99%